Revitalizing Urban Canyons Through Innovative Thermal Strategies - Rishabh Anand (International Journal of Urban Design and Development, 2025)
Urban canyons, environments very densely made up of tall buildings clustered on narrow streets, are treacherous when it comes to considerable heat retention and greatly increase wind speeds. The resulting conditions fuel the Urban Heat Island effect. That means urban canyons feel very hot and this of course harms both comfort and health of those who dwell in them. This research tackles the serious issue of discomfort due to heat in canyons by setting a set of design guidelines that reduce UHI effects and create a healthier microclimate. This study digs deep into a set of important thermal influences relating to urban canyons. Things like the sun give off heat, how surfaces reflect that heat were analyzed. This review leads to some principles to do a good design of buildings and landscapes that reduce heat build up. By presenting a review that uses solid evidence to reduce effects of Urban Heat Islands (UHIs), this contributes to urban design and landscape architecture and provide practical solutions to create urban spaces that are both thermal resilient and livable.
Keywords: Pedestrian Comfort; Pollutants Reduction; Street Design; Urban Canyons; Urban Design